Peran Mahasiswa Kampus Mengajar Angkatan Lima dalam Adaptasi Teknologi di SD Inpres Bistio - Amriani Amriani; Siti Suryani; Nurul Fitriani (Universitas Maritim AMNI Semarang, 2023)
This article aims to explain and describe the Teaching Campus Program which is one form of implementing the IndependentThis article aims to explain and describe the Teaching Campus Program which is one form of implementing the Independent Learning Campus (MBKM) in the form of teaching assistance to empower students in assisting the learning process in elementary schools in various villages/cities, one of which is SDI Bistio which is located in Masebewa, Sikka Regency, NTT. In this program, students involved have the responsibility to assist the school in the teaching process, assist with technology adaptation, and assist school administration. The purpose of this research is to find out the role of students in adapting technology at SDI Bistio, especially in using the Zoom and Google Meet learning applications. This research is a qualitative descriptive research. The data collection techniques used are interview and observation techniques. Data analysis includes (1) data reduction, (2) data presentation as well as drawing conclusions and verification. The result of this program is an increase in the knowledge of SDI Bistio teachers and students in terms of using the Zoom and Google Meet applications. This activity is limited to training students so long-term follow-up activities are needed to support technology adaptation at SDI Bistio.